(untitled) (Numerus academy review, 2026)
Cybercrime is a new crime that emerged with the down of informatics and expands the fields of using the internet, with the aim of attacking data in its broad technical significance, or using it to commit crimes that simulate traditional crimes in the virtual world, which are crimes threatening contemporary society with great risks that are difficult to discover; because this crime can be easily hidden and traveling across the world, without going through border checkpoints, and without the need to also show official documents or record personal data, so that it is committed by smart criminals who possess the methodology of technical knowledge, obliterate their evidence, change their positions, and return to strike again. Therefore, this study aims to research in defining the concept of an information criminal, while showing the most important features and characteristics of it.